Aktivitas Antiinsomnia dari Beberapa Ekstrak Tanaman Terhadap Mencit - HANUM FIRDAUSYA (Fakultas Farmasi, Universitas Padjadjaran, 2021)
Insomnia is a symptom that is characterized by having difficulty sleeping, restless sleep and often wake up at night. Insomnia can occur due to a problem that afflicts life or from several illnesses suffered by someone. The use of plants used to treat and prevent various diseases has been used since time immemorial. The active compounds contained in plants are usually responsible for their biological properties which are used for various purposes in medicine and prevention. Based on searches, some plant extracts have antiinsomnia activity with different dosages and concentrations. Further investigation still needs to be in an effort to provide scientific and development information about plants that have the potential to have antiinsomnia activity.Keywords: Insomnia, Plants, Hypnotic-Sedative Drugs